Determinação de cepas de Wolbachia em populações naturais de Solenopsis spp. (Hymenoptera: Formicidae) analisadas via Multilocus Sequence Typing (MLST): diversidade genética, coevolução e recombinação - Martins, Cíntia [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Insects/microorganisms interactions are broad and occurs in many different ways with symbiont bacteria of insects playing many roles, most unknown, on the biology if its host. What was considered a single eukaryotic organism is actually an aggregate of many different organisms which lead to a change in the way we study organisms, leading to a more holistic approach. Within this vast but relatively unknown world of microorganisms in association with insects are the bacteria of the genus Wolbachia (Class Alphaproteobacteria, Order Rickettsiales) widely distributed in arthropods and maternally transmitted, causing several reproductive alterations in the host, and their occurrence in natural populations being of great interest in the biological control of insects. Its distribution in ants is poorly explored and little is known about the interaction with the Solenopsis genus which includes native species from South America. This genus includes species cosmopolitan distributed and in Brazil they are widely distributed being preferentially associated with areas of human activity. This study aimed to analyze the genetic diversity of samples of nests from native populations of Solenopsis species infected by Wolbachia by sequencing the five genes comprising the Wolbachia multilocus, and also the wsp gene in order to characterize the strains and establish phylogenetic inferences between them. Furthermore test the hypothesis of coevolution between ants and its Wolbachia strains and recombination between found strains. With the sequencing and analysis of five genes comprising the Wolbachia multilocus (gatB, coxA, hcpA, ftsZ e fbpA) totaling 2079 bp the following results are highlighted: i. the record of 15 previously unknown new strains, ii. the record of 11 previously unknown new alleles, iii. phylogenetic relationship between the strains found here presents a polyphyletic pattern, indicative of the complexity of the evolutionary history of strains ...

Interações insetos/micro-organismos são amplas e ocorrem das mais diversas maneiras, com as bactérias simbiontes de insetos desempenhando vários papéis, na maioria desconhecidos, na biologia do hospedeiro. O que se considerava apenas um único organismo eucariótico é na verdade um agregado de vários diferentes organismos, o que levou a uma mudança na maneira de se estudar esses organismos, culminando em uma abordagem mais holística. Dentro desse vasto mundo, relativamente pouco conhecido dos micro-organismos em associação com insetos, estão as bactérias do gênero Wolbachia (Classe Alphaproteobacteria, Ordem Rickettsiales), amplamente distribuídas nos artrópodes e transmitidas maternalmente, causadoras de diversas alterações reprodutivas no hospedeiro, sendo que sua ocorrência em populações naturais pode ser de grande interesse no controle biológico. A distribuição dessas bactérias em formigas é pouco explorada e existe carência de informações sobre a interação com formigas do gênero Solenopsis, que inclui espécies nativas da América do Sul. Este gênero possui espécies distribuídas de forma cosmopolita e no Brasil estão amplamente disseminadas, associadas preferencialmente a áreas de atividade humana. Este trabalho teve como objetivo analisar a diversidade genética da Wolbachia de amostras de ninhos de populações nativas de espécies do gênero Solenopsis, através do sequenciamento de cinco genes que compõe o multilocus de Wolbachia, além do gene wsp, a fim de caracterizar as cepas e estabelecer inferências filogenéticas entre elas. Além disso, testar as hipóteses de coevolução entre as cepas e as formigas e de recombinação entre as cepas encontradas. Com o sequenciamento e análises dos cinco genes que compõem o multilocus de Wolbachia (gatB, coxA, hcpA, ftsZ e fbpA), totalizando 2079 pb, destacam-se os seguintes resultados: i. o registro de 15 novas cepas; ii. o registro de 11 alelos...
Keywords: Ants; Formiga; Simbiose; Filogenia